The Development of Environmental Pollution Module by Implementing Laskar Kalpataru Program to Improve Environmental Care Attitude of The Students (Journal of Innovative Science Education, 2020)
The developed module is a module that implements the Laskar Kalpataru program aimed at knowing the eligibility of the module as an effort to improve environmental care attitudes, knowing the increasing of students’ independence in learning, and knowing the effectiveness of the developed module in improving student learning outcomes. By using research and development (R&D) method, the results of this study indicate that the module are appropriate to be used in accordance with the eligibility criteria of the National Education Standards Agency (BSNP). It is in accordance with the phase I assessment of getting "yes" answer on all aspects in the questions. In the second phase of assessment, an average percentage of content eligibility is 92.97%, the language eligibility is 90.83% and the presentation component is 90.3%. The application of module is effective to improve student learning outcomes and improve the environmental care attitude.